Estrategias Metodológicas para optimizar el periodo de adaptación escolar en los niños y niñas de primer año de educación general básica de la Unidad educativa Dr. José Jaramillo Montoya de la cuidad de Machala en periodo lectivo 2013-2014 - Armijos Alvarado, Betty Jeannette (2015)
Teaching is the most complex and complete profile profession as a transformation of man to life, this educator reality is subject to constant didactic and pedagogical changes, especially when we have the inclusion of children in school, and we understand that changes are subject great needs.The boy and girl in her early days of onset in school life shows panic insecurity or fear holding for a long time, the change of home or family environment to a different or odd half ago that the author worry your research to the process of adaptation to the educational environment,The proper or timely implementation of activities will make or student interested in learning the new environment in which it is located, the desire to discover their new place, presents possibilities to discover and have fun, make it off momentarily from their environment familiar than the time needed help to integrate the new medium. The shortcomings of pedagogy in the process of adapting the student in his early days at school creates interest, by the author of this work, to investigate and create a resource for solving needs and curriculum requirements considering the child behavior in the field of home.The teachers of the first year of preschool education annually are challenged to adapt their children to the institution who come from a familiar social environment, with this background, this paper has the research process, as needed, to address didactic elements to stimulate the child's adjustment to the classroom with their peers under the guidance of the teacher. With the required interpretation of the outcome of the investigation is to strengthen the process of adaptation of children with which it contributes to the educational process. The optimization of available resources to which the proposal adds, can enhance the teaching quality of the institution.